Unusual anogenital apocrine tumor resembling mammary-like gland adenoma in male perineum: a case report - Yoshioka Takako; Umekita Yoshihisa; Tanimoto Akihide; Hatanaka Kazuhito; Kanekura Takuro (BMC, 2010)
Abstract A rare case of an apocrine tumor in the male perineal region is reported. A dermal cystic lesion developed in the region between the anus and scrotum of a 74-year-old Japanese male. The cystic lesion, measuring 3.5 × 5.0 cm in size, was lined by columnar or flattened epithelium with occasional apocrine features and supported by a basal myoepithelium lining. A mural nodule, measuring 1 × 1.5 cm in size, protruded into the cystic space and consisted of a solid proliferation of tubular glands with prominent apocrine secretion and basal myoepithelial cells. Immunohistochemical examination showed that the luminal cells were partially positive for gross cystic disease fluid protein 15 and human milk fat globulin 1, and the basal myoepithelial cells were positive for alpha-smooth muscle actin and S-100 protein. Estrogen and progesterone hormone receptors were focally and weakly positive for luminal epithelium. Although no mammary-like glands were present in the dermis around the tumor, this unusual apocrine tumor has been suggested to be derived from male anogenital mammary-like glands and mimic a mammary-like gland adenoma in the male perineum.